Evidence summary: Wound management – hydrogel dressings without therapeutic additives - Watts, Robin; Frehner, Liz (2016)
Question: What is the best available evidence regarding the effectiveness of hydrogel dressings without additional therapeutic additives in the management of wounds? Background: Hydrogels are designed to rehydrate a wound depending on the wound moisture levels. They are available in different forms including sheets, amorphous gels and impregnated gauze. They are best used with wounds with no or minimal exudate as they do not have capacity to absorb large amounts of exudate due to their high water content (up to 96%).